Evaluating the impact of bilateral and multilateral official development assistance on economic growth in Zambia - Nsomi-Mukuka, Nonde (Graduate School of Business (GSB), 2021)
As a recipient of Official Development Assistance (ODA), the Republic of Zambia is considered one of the aid-dependent nations in Sub-Saharan Africa. Development assistance has been said to have had made absolutely no contribution to economic growth and development in the country on observation of the Gross Domestic Product (GDP) per capita figure over the years which indicates periods of stagnation in growth despite ODA receipts. Generally, this conclusion has in the past been drawn without consideration for, and appreciation of, the variations in the objectives and disbursement channels of ODA. Consequently, this study sought to investigate the separate impact of multilateral and bilateral ODA on GDP per capita which served as a proxy for economic growth and development in Zambia. Based on a modified neo-classical economic growth model that incorporates multilateral and bilateral ODA as determinants of economic growth, this study employed the ARDL model to investigate the long-run and short-run relationship between GDP per capita and ODA from 1975 to 2016. Two similar growth models were analysed substituting the net ODA variable with multilateral and bilateral ODA in order to assess the relationship. In addition to net ODA, the model included the variables investment, trade openness and the labour force as determinants of economic growth. Findings from the study show that multilateral ODA had a significant negative impact on GDP per capita, while the bilateral ODA model showed a statistically insignificant negative relationship. The findings of the study support the notion that different types of foreign aid cannot be expected to have a uniform impact on growth and development in terms of effectiveness. The recommendations point to the importance of re-evaluation of modalities by donors to ensure that development assistance is more effective in achieving sustainable development goals.